2021
DOI: 10.21475/ajcs.21.15.02.p2984
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest conservation of Tommy atkins mango fruits during storage using Moringa oleifera oil-based coating

Abstract: Among several biodegradable coatings used to extend the shelf life of fresh fruits, those that can be obtained from Moringa oleifera stand out due to their extraordinary biochemical, antibacterial and antifungal properties. Another aspect is their constitution which is composed of proteins, lipids, carbohydrates, carotenoids, vitamins, minerals and natural bioactive compounds, that can be applied for the development of functional foods due to their nutritional and pharmaceutical properties. The objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The changes in color in cucumbers are due to the conversion of the cucumber surface from a green to a more yellowish color [32]. The study by Silva et al [22] did not show any significant interactions between color and moringa oil coating in mango. They observed variations in the color of the fruits, specifically for those in the control treatment (without bio-based coating).…”
Section: Colormentioning
confidence: 86%
See 3 more Smart Citations
“…The changes in color in cucumbers are due to the conversion of the cucumber surface from a green to a more yellowish color [32]. The study by Silva et al [22] did not show any significant interactions between color and moringa oil coating in mango. They observed variations in the color of the fruits, specifically for those in the control treatment (without bio-based coating).…”
Section: Colormentioning
confidence: 86%
“…Similar results were found by Muddather and Abu-Goukh [39], who reported that the delay in TSS accumulation was further enhanced by the wax treatment. Coating mango with 0.5 and 1% moringa oil showed the best results for TSS values, as they presented the highest mean values [22]. El-Gioushy et al [40] found that the TSS content of 10% Gum Arabic-coated guava was lower compared to non-coated.…”
Section: Total Soluble Solids (Tsss)mentioning
confidence: 98%
See 2 more Smart Citations